Clinical Analysis of Pulmonary Nocardiosis in Patients With Autoimmune Disease. Issue 39 (September 2015) - Li, Shan; Song, Xin yu; Zhao, Yu yue; Xu, Kai; Bi, Ya lan; Huang, Hui; Xu, Zuo jun; Kumar., Anil
<x xml:space="preserve">Abstract</x> Abstract Nocardiosis is an opportunistic infection that most commonly involves the lung; however, only a few case reports of autoimmune disease complicated by pulmonary nocardiosis exist in the literature. We conducted a retrospective analysis of 24 cases of both autoimmune disease and pulmonary nocardiosis at the Peking Union Medical College Hospital between 1990 and 2012. Fifty-two cases were hospitalized with nocardiosis, 24 of whom had at least 1 autoimmune disease before the diagnosis of pulmonary nocardiosis. The cohort patients consisted of 5 men and 19 women, with a mean age of 44.2 years. All were negative for human immunodeficiency virus. All but 1 patient had received immunosuppressants, including corticosteroids, cyclophosphamide, azathioprine, methotrexate, or hydroxychloroquine. Fever (87.5%), cough (83.3%), and sputum (79.2%) were the most common clinical manifestations. Ten cases were accompanied by subcutaneous nodules and/or cutaneous abscesses, and 4 had brain abscess. Half of them were lymphocytopenic. Thirteen of the 16 cases who underwent lymphocyte subtype analysis had decreased CD4+ T-cell counts. Nineteen cases had decreased serum albumin levels. Nocardia was isolated from sputum (13/24), bronchoalveolar lavage fluid (4/6), lung tissue (5/6), pleural effusions (3/5), skin or cutaneous pus (7/10), and brain tissue (1/1). The most common imaging findings were air-space opacities (83.3%), followed by nodules (62.5%), cavitations (45.8%), and masses (37.5%). Five were administered co-trimoxazole only, and the others were treated with 2 or more antibiotics. All 5 cases with skin abscesses and 2 of the 4 cases with brain abscesses were treated by surgical incision and drainage. None underwent thoracic surgery. Corticosteroid dosages were decreased in all cases, and cytotoxic agents were discontinued in some cases. Twenty-two cases recovered, and 2 died. Pulmonary nocardiosis associated with an underlying autoimmune disease showed a female predominance and presentation at younger age. Immunosuppressant therapy, lymphocytopenia, particularly low CD4+ T-lymphocyte counts, and low serum albumin levels may be disease susceptibility factors. Air-space opacities and nodules were the most common chest imaging features, and disseminated nocardiosis with lung and skin involvement was more common among them. Early diagnosis and anti-nocardial antibiotics with modulation of the basic immunosuppressive therapy were important for them.